A CASE STUDY ON 3 WEEKS PREMATURE RUPTURE OF MEMBRANES CAUSED BY OROPHARYNGEAL MICROBIOTA - SM ALKASSEH, AREEFA; ALKHATIB, SHAIMAA JAMAL (Innovare Journal Health Sciences, 2021)
Premature rupture of membrane (PROM) is produced when amniotic membranes tear before labor onset and is recorded in around 8 % of full-term gestations. Preterm PROMs (PPROMs) take place before the 37th week of gestation, with an incidence of 2–4 % of pregnancies, and it is associated with higher maternal and perinatal morbidity and mortality, mainly related to infectious processes and prematurity. Among maternal complications, which include postpartum infection, premature placental detachment, and maternal sepsis, we highlight clinical chorioamnionitis for its incidence and severity. Of decreasing frequency, perinatal complications include respiratory distress, neonatal sepsis, intraventricular hemorrhage, necrotizing enterocolitis, and neurological lesions. Full-term PROM frequently has a physiological cause and is a consequence of uterine contractions; however, PPROM usually has a multifactorial etiology that is often unknown, although the most frequently reported cause is an infection, observed in up to 60 % of cases. Therefore, the etiology of PPROM, although probably infectious, remains unknown in most cases. The obstetric approach varies as a function of gestational age, actively inducing the pregnancy in full-term PROM but performing an overall evaluation of maternal-fetal status in PPROM. In the latter situation, an assessment is made of the relative risks and benefits of a wait-and-see attitude versus pregnancy induction, considering signs of infection and/or prematurity, and ordering antibiotic treatment when PPROM is diagnosed . Multiple combinations of antimicrobial drugs have been proposed and better perinatal and maternal outcomes have been reported for the prophylactic administration of some new combinations. This study describes a case of PPROM caused by urinary tract infection.